O corpo: entre o sofrimento e a criatividade - Porchat, Patricia [UNESP] (Universidade do Estado do Rio de Janeiro, Instituto de Medicina Social, 2014)
Bodily and gender subjective experiences challenge Psychoanalysis to reconsider its conceptual apparatus and to sustain an ethics which enables a careful and attentive listening. It puts into question the existence of a taboo in relation to the body that would prevent this listening. Bodily interventions and changes observed in transsexuals and transgender people experiences have been the subject of efforts to approximate Psychoanalysis and Queer Theory. We believe that this approximation will bring us the possibility to formulate concepts that might clear up the understanding of these experiences. In order to investigate the status of the body we separate it from gender and sexual norms by choosing three interlocutors: psychiatry - the hormone treatment of adolescent transsexuals; art and biotechnological feminism. This way of considering things allows us to take into account different aspects of deconstruction and reconstruction of the body.

As experiências subjetivas corporais e de gênero colocam para a psicanálise o desafio de questionar seu aparato conceitual e de sustentar uma ética que permita a manutenção de uma escuta cuidadosa e atenta. Problematizamos a existência de um tabu em relação ao corpo que impediria essa escuta. As intervenções e modificações corporais que encontramos nas experiências de transexuais, travestis e transgêneros têm sido objeto de esforços no sentido de aproximar a psicanálise da teoria queer, pois aí residiria a possibilidade de formular concepções que iluminem a compreensão dessas experiências. Interrogamos o estatuto do corpo de maneira isolada das normas de gênero e sexuais e elegemos como interlocutores a psiquiatria - na situação de hormonização de adolescentes -, a arte e o feminismo biotecnológico. O olhar diferenciado nos permite considerar variados aspectos da desconstrução e reconstrução do corpo.
Keywords: Body; transsexuality; gender; queer theory; Corpo; transexualidade; gênero; teoria queer